NARASI REVITALISASI PADA PERSPEKTIF PENDIRI JEMBER FASHION CARNAVAL - Gati Dwi Yuliana (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Narrative is the essence of human form of communication. Jember Fashion Carnival (JFC) chose a fashion carnival as a medium for telling stories about social struggles that became his dream. This study focuses on how JFC builds a narrative story at each of its carnival events. So that this research is expected to be able to comprehensively explain how a carnival builds a narrative through a storytelling approach as an effort to revitalize the arts in order to maintain the sustainability of a tourism program. This study uses the theory of the narrative paradigm to explain how individuals create meaning in life through dialogue in various mediums. This study uses a qualitative approach, Case study Methode with interview techniques. Research informants are representatives of JFC management. The results of the study show that the way JFC builds its main narrative is by appointing the figure of Dynand Fariz himself as the founder. This is because Dynand Fariz forms his figure as a narrator who tells a story about himself and manifests all his thoughts in all carnival events. The story about the figure of Dynand Fariz melts into a series of carnival defiles that describe the ideals, dreams, and struggles to return the carnival to its essence as an art performance.